Analisis rasio aktivitas keuangan pada masa covid-19 terhadap laba bersih - Krismonika, Septiana Dwi; Rosita (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to analyze the effect of partial and simultaneous accounts receivable turnover, fixed assets, total assets and inventories on net profit of food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the period 2018-2020 before and during the occurrence of Covid-19. This research is a quantitative research using secondary method in the form of annual financial report data of food and beverage sub-sector companies with sampling through www.idx.co.id selected through a purposive sampling method. The population in the study is 56 companies in the food and beverage sub-sector consumer goods listed on the Indonesia Stock Exchange in 2020. The sample in this study is the food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the 2018-2020 period with as many as 42 companies using data analysis techniques. multiple regression and perform classical assumption test with SPSS application. The results of this study indicate that the accounts receivable turnover, fixed asset turnover and total asset turnover partially affect net income, while inventory turnover partially have no effect on net income. In addition, simultaneously accounts receivable turnover, fixed asset turnover, total asset turnover and inventory turnover have effect on net income.